MORPHOLOGICAL AND MOLECULAR PHYLOGENY OF ANOPLOCEPHALIDEAN CESTODE PARASITE FROM CAPRA HIRCUS(L) IN SOLAPUR DISTRICT (M.S.) INDIA (Journal of Pharmaceutical Negative Results, 2022)
Cestode Parasite are collected from intestines of Capra hircus (L) in Solapur district (M.S.) India, were subjected to a complete parasitological examination. The present Cestode that is MonieziaSp. differ from all known species is having the scolex quadrangular, mature segments nearly four times broader than long, number of testes, shape of ovary, number of Inter proglottidal gland and their arrangement. In morphological data the Cestode is identified as confirmed to be representing Moniezia species in mammalian host goat. Identity of Cestode Parasites was confirmed through amplification and sequencing of COI- 5P gene marker (by molecular characterization) Phylogentic analysis of COI-5P gene marker of MoneiziaSp. showed that it is cladded with Monieziaexpansa.